A REVIEW OF ELECTRIC VEHICLES: THEIR IMPACT ON THE ELECTRICITY GRID AND ARTIFICIAL INTELLIGENCE-BASED APPROACHES FOR CHARGING LOAD MANAGEMENT - Çetin, Muhammed Sefa; Gençoğlu, Muhsin Tunay; Şahin, Habip (Zülküf GÜLSÜN, 2024)
The widespread use of electric vehicles contributes significantly to environmental sustainability by reducing the use of fossil fuels. However, the increasing number of electric vehicles and the intense charging demand may cause negative impacts such as overloading, voltage fluctuations and energy supply-demand imbalances in electricity grids. In this paper, artificial intelligence-based methods applied for the management of the negative impacts of electric vehicles on the grid are discussed comprehensively and artificial intelligence approaches in the literature used to manage electric vehicle charging load are analysed. Among these approaches, energy management strategies based on charging demand forecasting, dynamic pricing, routing, charging scheduling and smart grid integration are analysed in detail. This paper summarises the latest innovative AI-based solutions developed to manage the charging load of electric vehicles, improve grid stability, increase charging service price prediction accuracies, maximise grid and user satisfaction, ensure load balance, reduce charging and operating costs, reduce energy consumption and optimise power flow. This paper contains comprehensive and qualified information about the bilateral (grid and user perspective) management algorithms of the charging load of electric vehicles.
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)